Impact of Preadmission Observation Hours on Key Physical Therapist Clinical Education Stakeholders: Quantitative Analysis. Issue 4 (8th December 2022) - Bayliss, Jamie; Schack-Dugre, Judi; Hoang, Thuha; Watkins, Molly; Mitchell, Katy; Mariano, Mira; Greco, Jamie; Colgrove, Yvonne; Wheeler, Emma; Kiyota, Hiroshi; Pientok, Colette; Stephens, Laura; et al.
Abstract : Introduction and Review of Literature: Physical therapist (PT) and PT assistant (PTA) education programs have historically required preadmission observation hours (ObHr) as an admission requirement. The variability of conditions surrounding ObHr lends itself to investigation. The aims of this study were to (1) identify the perceived value of ObHr to Admission Committee (AC) members, Directors of Clinical Education, current Doctor of Physical Therapy (DPT) students, and PT clinicians, (2) examine the effect that ObHr have on the decision-making process of AC members, and (3) examine the effect that ObHr had on current DPT students' decisions to pursue a PT career. Subjects: Four stakeholder groups were targeted (N = 4, 471). Methods: This descriptive, cross-sectional study utilized surveys to collect quantitative and qualitative data through closed-ended and open-ended questions. This article encompasses the analysis of the quantitative components by analyzing fixed responses on stakeholder surveys. Qualitative findings are reported in a separate article. Results: Perceived purposes of ObHr by stakeholders were as follows: (1) to gain an accurate understanding of the depth and breadth of the profession, (2) to confirm a desire to pursue PT as a profession, and (3) to better understand the roles and responsibilities of PT. The number of necessary ObHr varied among the groups ranging from 0 to 100 hours. Student perception that completing more hours than required would assist in their favorability for acceptance was debunked. Discussion: There was consensus among all groups regarding the perceived purposes. Variability of stakeholder perception of necessary ObHr to achieve goals was revealed. Doctor of Physical Therapy programs should be transparent and clarify the purpose and quantity of required ObHr. Conclusion: Long-standing requirements could be taxing current resources and limiting entry into the profession. Determining the minimum number of necessary ObHr, considering virtual methods, and employing distinct transparency on how ObHr are used in the decision-making process are opportunities for further study to address these issues.